2009
DOI: 10.1007/s00167-009-0818-9
|View full text |Cite
|
Sign up to set email alerts
|

Physiological anterior laxity in healthy young females: the effect of knee hyperextension and dominance

Abstract: Female athletes are more likely to sustain an anterior cruciate ligament (ACL) injury. Knee laxity, hyperextension and limb dominance have been suggested as possible factors contributing to the knee injury. The aims of this study were to investigate the physiological anterior knee laxity between the dominant and non-dominant limb and in healthy young females with and without hyperextension knees. Forty-two healthy young females, 21 with hyperextension knees, were recruited voluntarily for this study. The subje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
10
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 22 publications
4
10
0
Order By: Relevance
“…Consistent with the findings of previous studies [3,12], our study revealed the little evidence for laterality of hypermobility in school-aged children.…”
Section: Discussionsupporting
confidence: 92%
“…Consistent with the findings of previous studies [3,12], our study revealed the little evidence for laterality of hypermobility in school-aged children.…”
Section: Discussionsupporting
confidence: 92%
“…In our study, there was little evidence for laterality of hypermobility, consistent with the findings of one previous small study but in contrast to another (22, 23). In addition, there was no evidence of an association with ethnicity, although only a small proportion of the ALSPAC cohort is nonwhite (3.7%).…”
Section: Discussionsupporting
confidence: 91%
“…There is also a suggestion that ethnic background can influence hypermobility (16, 17) and that generalized joint laxity is more common in ballet dancers (18), musicians (19), gymnasts (20), and swimmers (21). Contradictory results from some small studies have demonstrated greater degrees of joint laxity in either the dominant limb (22) or the nondominant limb (23). A lack of association with body weight has been reported consistently (8, 24, 25).…”
mentioning
confidence: 99%
“…14 The risk factors that predispose a person to an ACL injury vary. It is well known that many knees passively extend past 0 degrees and that some, but not all, of these knees may have generalized laxity 9,1315,23 . Knee hyperextension (HE) has been previously reported to be an intrinsic factor contributing to ACL injury 13,14 .…”
Section: Introductionmentioning
confidence: 99%